TCF2/HNF‐1beta mutations: 3 cases of fetal severe pancreatic agenesis or hypoplasia and multicystic renal dysplasia. (January 2014) - Body‐Bechou, Delphine; Loget, Philippe; D'Herve, Dominique; Le Fiblec, Bernard; Grebille, Anne‐Gaelle; Le Guern, Hélène; Labarthe, Caroline; Redpath, Margaret; Cabaret‐Dufour, Anne‐Sophie; Sylvie, Odent; Fievet, Alice; Antignac, Corinne; et al.
ABSTRACT Objective The aim of this study was to document the association between pancreatic agenesis or hypoplasia and multicystic renal dysplasia related to transcription factor 2 (TCF2) or hepatocyte nuclear factor 1 beta mutations. Methodology We describe the phenotype of the pancreas and the kidneys from three fetuses heterozygous for a mutation of TCF2. Cases Case 1 had bilateral hyperechogenic, multicystic kidneys, bilateral clubfoot and pancreatic agenesis. Case 2 had two enlarged polycystic kidneys, anamnios and pancreatic agenesis. Case 3 had multicystic renal dysplasia, oligohydramnios and hypoplasia of the tail of the pancreas. Conclusion TCF2 mutations are frequently discovered in fetuses presenting with bilateral hyperechogenic kidneys. The association between pancreatic agenesis and a TCF2 mutation has not previously been reported. TCF2 deficiency in mice leads to pancreatic agenesis, suggesting that the gene is essential for pancreatic development. Our observations indicate the importance of visualizing the pancreas during ultrasound examinations if renal malformations are discovered. © 2013 John Wiley & Sons, Ltd.